A new remarkable species of the genus Hyperlais Marion, 1959 (Lepidoptera: Crambidae) from Kyrgyzstan - Korb, Stanislav K.; Gorbunov, Pavel Yu.; Melyakh, Sergey F. (Zootaxa, 2023)
A new species, Hyperlais orodruinella sp. n., is described. Its type locality is “Kyrgyzstan, Fergansky Mts., Razan Say Valley, Sary-Bel stream, 41°25’16.74”N, 72°18’59.19”E, 892 m”. This new species differs from all other species of the genus by its patternless wings, by its very dark ground colour and by its male genitalia features, especially aedoeagus cornuti (it has three groups of cornuti instead of two groups in other species).